Predictors of adolescents' health‐promoting behaviors guided by primary socialization theory. Issue 4 (10th June 2013) - Rew, Lynn; Arheart, Kristopher L.; Thompson, Sanna; Johnson, Karen
Abstract: Purpose: The purpose of this study was to determine the influence of parents and peers on adolescents' health‐promoting behaviors, framed by primary socialization theory. Design and Method: Longitudinal data collected annually from 1, 081 rural youth (mean age = 17 ± 0.7; 43.5% males; 44% Hispanic) and once from their parents were analyzed using generalized linear models. Results: Parental monitoring and adolescent's religious commitment significantly predicted all health‐promoting behaviors (nutrition, physical activity, safety, health practices awareness, and stress management). Other statistically significant predictors were parent's responsiveness and health‐promoting behaviors. Peer influence predicted safety and stress management. Practice Implications: Nurses may facilitate adolescents' development of health‐promoting behaviors through family‐focused interventions.